Cell‐autonomous defense, re‐organization and trafficking of membranes in plant–microbe interactions. Issue 4 (28th August 2014) - Dörmann, Peter; Kim, Hyeran; Ott, Thomas; Schulze‐Lefert, Paul; Trujillo, Marco; Wewer, Vera; Hückelhoven, Ralph
Summary: Plant cells dynamically change their architecture and molecular composition following encounters with beneficial or parasitic microbes, a process referred to as host cell reprogramming. Cell‐autonomous defense reactions are typically polarized to the plant cell periphery underneath microbial contact sites, including de novo cell wall biosynthesis. Alternatively, host cell reprogramming converges in the biogenesis of membrane‐enveloped compartments for accommodation of beneficial bacteria or invasive infection structures of filamentous microbes. Recent advances have revealed that, in response to microbial encounters, plasma membrane symmetry is broken, membrane tethering and SNARE complexes are recruited, lipid composition changes and plasma membrane‐to‐cytoskeleton signaling is activated, either for pre‐invasive defense or for microbial entry. We provide a critical appraisal on recent studies with a focus on how plant cells re‐structure membranes and the associated cytoskeleton in interactions with microbial pathogens, nitrogen‐fixing rhizobia and mycorrhiza fungi.